Інваріантна природа мотиву катарсису в поемі Леоніда Горлача «Ніч у Вишгороді» - Федько, Ольга; Fedko, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті здійснено спробу проаналізувати мотив катарсису в поемі Л. Горлача «Ніч у Вишгороді» відпо-відно до основних принципів універсально-культурного аналізу та психологічного потрактування концепту катарсису. Інваріантна природа цього мотиву проявляється під час зіставлення досліджуваної поеми Л. Горлача з романом у віршах Ліни Костенко «Берестечко», оскільки у цих творах утверджено потребу ду-ховного очищення в межовій ситуації. The article deals with the analysis of the motif of catharsis in L. Gorlach’s poem «Night in Vyshgorod». The man principles of cultural-universal analysis and the psychological concept of catharsis are observed. Motif of catharsis is central for this work, because L. Horlach shows Yaroslav the Wise as old, dying man, who is trying to reconsider his decisions, deeds, to find peace and forgiveness in order to come to God with a pure soul and conscience. The invariant nature of this motif is proved by the comparing of L. Gorlach’s poem «Night in Vyshgorod» with Lina Kostenko’s novel in verse «Berestechko». The similarities in the ideas of this literary works and their realizations are based on the necessity of relief and renewal before the beginning of important action, on the need to overcome doubts, feeling of defeat.
The Invariant Nature of the Motif of Catharsis in L. Gorlach’s Poem «Night in Vyshgorod».
Keywords: універсалія; універсально-культурний аналіз; катарсис; мотив; інваріант; universal; cultural-universal analysis; catharsis; motif; invariant